Telomere-to-telomere and haplotype-resolved genome assembly of the Chinese cork oak (Quercus variabilis) - Wang, Longxin; Li, Lei-Lei; Chen, Li; Zhang, Ren-Gang; Zhao, Shi-Wei; Yan, Han; Gao, Jie; Chen, Xue; Si, Yu-Jun; Chen, Zhe; Liu, Haibo; Xie, Xiao-Man; et al. (Frontiers in Plant Science, 2023)
The Quercus variabilis, a deciduous broadleaved tree species, holds significant ecological and economical value. While a chromosome-level genome for this species has been made available, it remains riddled with unanchored sequences and gaps. In this study, we present a nearly complete comprehensive telomere-to-telomere (T2T) and haplotype-resolved reference genome for Q. variabilis. This was achieved through the integration of ONT ultra-long reads, PacBio HiFi long reads, and Hi-C data. The resultant two haplotype genomes measure 789 Mb and 768 Mb in length, with a contig N50 of 65 Mb and 56 Mb, and were anchored to 12 allelic chromosomes. Within this T2T haplotype-resolved assembly, we predicted 36,830 and 36,370 protein-coding genes, with 95.9% and 96.0% functional annotation for each haplotype genome. The availability of the T2T and haplotype-resolved reference genome lays a solid foundation, not only for illustrating genome structure and functional genomics studies but also to inform and facilitate genetic breeding and improvement of cultivated Quercus species.